Carbon dioxide as a reagent and solvent - Streng, Emilia S. (2017)
The work described in this Thesis has been carried out within the Erasmus Mundus framework for Sustainable Industrial Chemistry (SINCHEM). The work concentrates on the possible utilisation of carbon dioxide as a solvent and as a starting material. Chapter 1 introduces carbon dioxide and its utilisation. In addition, the 12 Principles of CO2 Chemistry are presented, as well as continuous flow chemistry and self-optimising reactors. The relevant aspects of these reactors are discussed further in Chapter 2. The results of the research are presented in Chapters 3-6. A self-optimising reactor with FT-IR analysis was employed for the methylation of alcohols as explained in Chapter 3. Chapters 4-6 concentrate on N-alkylation reactions. In Chapter 4, the reactivity between aniline, tetrahydrofuran and dimethyl carbonate in supercritical carbon dioxide is discussed. This research led to the discovery of novel transformations. In Chapters 5 and 6, methanol was employed to methylate amines. A ruthenium triphosphate catalyst, which can produce methanol from carbon dioxide and hydrogen, was used to catalyse the reactions between methanol and aliphatic amines, as described in Chapter 5. Also the cyclisation and subsequent methylation of amino alcohols was studied. This reactivity is also the topic of Chapter 6, where γ-alumina was used as catalyst and supercritical carbon dioxide as solvent. Finally, Chapter 7 summarises the work described in this Thesis and evaluates the progress made towards achieving the aims that are introduced at the end of Chapter 1. One of these aims is to evaluate the work carried out in this Thesis according to the 12 principles of CO2 Chemistry. This evaluation is shown in Chapter 7.